2006
DOI: 10.1016/j.rmed.2006.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled nitric oxide as a diagnostic test for asthma in rhinitic patients with asthmatic symptoms

Abstract: Measuring FE(NO) may be useful for the screening of rhinitic patients with asthma-like symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 24 publications
3
34
0
Order By: Relevance
“…Adults, adults plus adolescents, all age groups and unspecified age groups ), adults plus adolescents (three studies, four citations [82][83][84][85] ), all age groups (three studies, three citations [86][87][88] or an unspecified age range (three studies, three citations 89,90,92 ). Table 21 summarises the characteristics of the studies and provides a brief description explaining their relevance to the decision problem (note: Schneider et al 71,72 appears twice in this table as this study reported two differently defined populations).…”
Section: Diagnostic Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Adults, adults plus adolescents, all age groups and unspecified age groups ), adults plus adolescents (three studies, four citations [82][83][84][85] ), all age groups (three studies, three citations [86][87][88] or an unspecified age range (three studies, three citations 89,90,92 ). Table 21 summarises the characteristics of the studies and provides a brief description explaining their relevance to the decision problem (note: Schneider et al 71,72 appears twice in this table as this study reported two differently defined populations).…”
Section: Diagnostic Reviewmentioning
confidence: 99%
“…l Nine studies 54,[69][70][71][72][82][83][84]86,87,90 recruited patients with symptoms of asthma who were broadly equivalent to patients entering the UK pathway at position A (see Figure 8). Of these, six 69,71,72,[82][83][84]86,87 were considered to be of most relevance to the decision problem, although the studies had not necessarily been conducted in the UK.…”
Section: Studies Meeting the Inclusion Criteriamentioning
confidence: 99%
See 3 more Smart Citations